Interference of Regional Languages on Indonesian Language in Students' Speech at PP. Madrasatul Qur'an Tebuireng Jombang - Muhammad Qowiyyul Amin; Yulianah Pihatin (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe the types of regional language interference in oral use and analyze the factors that influence it in students at the Madrsatul Qur'an Tebuireng Jombang Islamic Boarding School. As a community with many languages, students use Indonesian in formal situations and Javanese in everyday interaction. This intensive language interaction causes interference. The method applied in this study is descriptive qualitative. Data were collected using participatory observation methods (simak lebat cakap), recording, and in-depth interviews. The data obtained were analyzed by identifying, classifying, and describing the forms and factors causing interference. The results of the study revealed four types of interference, namely (1) phonological interference, which is a change in phoneme pronunciation; (2) morphological interference, especially in the use of affixes; (3) lexical interference, through the addition of Javanese vocabulary; and94) syntactic interference, which affects sentence structure. The main factors that trigger interference include (1) the habit of using the first language (B1), (2) the domicile of the Indonesian language environment, (3) limited mastery of Indonesian vocabulary, and (4) pragmatic factors to express closeness and solidarity between students.